Automotive sketching: techniques employed by industrial design students at diploma level in Universiti Teknologi Mara Kedah / Zaidi Yusoff - Yusoff, Zaidi (2016)
Sketches usually convey useful information regarding the desired shape, style, image, identity in the discipline of Automotive Design. Therefore designers place huge emphasis on concept development and styling activities. In fact as the decisions made during these stages are keys to the product's success. In recent research regarding to automotive design sketches, it seems are no such a standard that can be used and generalized by a designer in producing systematic design sketches. This research tries to understand on how designer use their skills and strategies in producing a purposeful automotive design sketches. The used of quantitative and qualitative research method through automotive design students at diploma level at the Universiti Teknologi MARA Kedah has revealed a standard and providing a guideline to a beginner designer. Among the findings: 1) Every designer is different and their abilities of producing sketches is depending on their individual skill; 2) There are positive corrections on designer perception in interpretation of materials, form elements, features, components, views of cars, sketching strategies and reflection of minds; 3) In the evaluation of form structure through sketches between superior level to low level of complexity, it is shows that there are a consistency pattern by a designer such as selectivity and determination on focal area at form design by designers. In conclusion, these findings are expected to be used as a guideline and strategy for a beginner designer to understand the knowledge in producing systematic automotive design sketches.